2012
DOI: 10.1007/s11010-012-1464-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of gallic acid isolated from Peltiphyllum peltatum against sodium fluoride-induced oxidative stress in rat’s kidney

Abstract: In the present study, the nephroprotective effect of gallic acid isolated from Peltiphyllum peltatum was examined in sodium fluoride (NaF) treated rats. Nephrotoxicity was induced by 1-week intoxication of NaF at 600 ppm through drinking water. The levels of thiobarbituric acid reactive substances, reduced glutathione as well as activities of superoxide dismutase and catalase in renal tissues homogenates were determined. The serum biochemical markers of renal injuries including creatinine, serum urea, blood ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 37 publications
7
39
0
Order By: Relevance
“…However, the protective role exerted by taurine in fluorideexposed rats is mediated through decreases in LPO as well as augmentation of SOD and CAT activities in the kidneys of the rats. The diminution in the GSH level in fluoride-treated rats is in line with previous studies [33]. Fluoride is absorbed from the stomach as hydrofluoric acid which could oxidize thiol group and consequently lead to decrease in GSH level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the protective role exerted by taurine in fluorideexposed rats is mediated through decreases in LPO as well as augmentation of SOD and CAT activities in the kidneys of the rats. The diminution in the GSH level in fluoride-treated rats is in line with previous studies [33]. Fluoride is absorbed from the stomach as hydrofluoric acid which could oxidize thiol group and consequently lead to decrease in GSH level.…”
Section: Discussionsupporting
confidence: 91%
“…The biochemical data on the chemoprotective influence of taurine on fluoride-induced toxicity is well supported by the histological evaluation evidenced by the normalcy in the renal architecture of rats co-exposed to fluoride and taurine. In comparison with earlier studies, high concentration of NaF (600 mg NaF/L) for 7 days was used to induce renal toxicity [33], whereas the present study utilized very low concentration of NaF (15 mg NaF/L) for 45 days to induce renal and thyroid toxicities. The significant toxic effects of low dose of NaF observed in the present study may be attributed to the longer duration of exposure when compared with earlier study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our fi nding that gallic acid effectively protected rat erythrocytes suggests that the antioxidant effect of the compound at the tested dosage in vivo was more prevalent than its prooxidative effects. The ameliorative effect of gallic acid on lipid peroxidation in vivo was also in agreement with other studies (35,36,37,38). Although Li et al (36) revealed the potential of gallic acid in increasing the GSH/oxidized glutathione (GSSG) ratio in senescence-accelerated mice, our result appears to be the fi rst evidence on the benefi cial effect of gallic acid on in vivo NaF-mediated oxidative stress in rat erythrocytes.…”
Section: Figure 4 Effects Of Gallic Acid and Vitamin C On Gshsupporting
confidence: 93%
“…Hence, gallic acid bearing optimised catecholic functional groups (Figure 2) is one of by far the most potent antioxidant compounds we have characterised to date in various biological systems both in vitro and in vivo. Increasing the structural complexity of these compounds does not also seem to offer more potency in many biological systems as we have demonstrated in several studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Furthermore, gallic acid and its derivatives display numerous other pharmacological effects that make them potential drug candidates from anticancer/chemopreventive agents to complex metabolic disease inhibitors.…”
Section: Smart Drugs For Complex Diseasesmentioning
confidence: 99%